Shock waves and Cerenkov radiation in electromagnetic substratum - H. E. Wilhelm (International Journal of Mathematics and Mathematical Sciences)
The EM fields of charged particles moving with velocity v in a physical vacuum with wave carrier (substratum) are determined by means of the generalized, Galilei covariant Maxwell equations for inertial frames ∑. with substratum flow w. In this Galilean approach, all velocities have absolute meaning relative to the substratum rest frame ∑o, and the relative velocity of material particles is given by the linear Galilean relation vG=v1−v2, permitting in principle superluminal relative velocities |vG|>co. Inter alias, the possibility of EM shock waves and Cerenkov radiation in the vacuum substratum is discussed. Experiments are proposed to test the theoretical predictions.